2017
DOI: 10.1038/s41598-017-04435-9
|View full text |Cite
|
Sign up to set email alerts
|

First integrative trend analysis for a great ape species in Borneo

Abstract: For many threatened species the rate and drivers of population decline are difficult to assess accurately: species’ surveys are typically restricted to small geographic areas, are conducted over short time periods, and employ a wide range of survey protocols. We addressed methodological challenges for assessing change in the abundance of an endangered species. We applied novel methods for integrating field and interview survey data for the critically endangered Bornean orangutan (Pongo pygmaeus), allowing a de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
65
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 56 publications
(68 citation statements)
references
References 63 publications
3
65
0
Order By: Relevance
“…As the species has also become a global icon for biodiversity conservation efforts in the face of the rapid and continued expansion of industrial oil palm plantations (Struebig et al 2015), we would expect a stasis or at lease, a reduced rate of loss of orangutan population in RSPO certified concessions, attributable to RSPO status. We used a recently developed dynamic and spatially-explicit population distribution and density map, developed by Santika et al (2017), overlayed with concession boundary maps, to ascertain the presence and density of orangutans in palm oil concessions between 1999 and 2014. Santika et al predicted orangutan population estimates are based on Bayesian modelling that takes into consideration various input data (helicopter nest counts, transect nest counts, and interview data) and predictors.…”
Section: Environmentmentioning
confidence: 99%
“…As the species has also become a global icon for biodiversity conservation efforts in the face of the rapid and continued expansion of industrial oil palm plantations (Struebig et al 2015), we would expect a stasis or at lease, a reduced rate of loss of orangutan population in RSPO certified concessions, attributable to RSPO status. We used a recently developed dynamic and spatially-explicit population distribution and density map, developed by Santika et al (2017), overlayed with concession boundary maps, to ascertain the presence and density of orangutans in palm oil concessions between 1999 and 2014. Santika et al predicted orangutan population estimates are based on Bayesian modelling that takes into consideration various input data (helicopter nest counts, transect nest counts, and interview data) and predictors.…”
Section: Environmentmentioning
confidence: 99%
“…Recent population trend studies indicate that killing—whether through hunting, poaching or conflict—is one of the key drivers of orangutan extinction on Borneo, with the largest absolute declines noted for areas where no or limited deforestation is taking place (Santika et al, ; Voigt et al, ). These insights are not yet widely accepted in the orangutan conservation community (Sherman et al, ).…”
Section: Current Developments In Orangutan Conservation: a State‐of‐tmentioning
confidence: 99%
“…have increased by more than 10% in Indonesia from 2015 to 2017, exceeding the government target of an annual 2% population increase [1]. This assessment is in strong contrast with recent publications that showed that the Bornean orangutan (P. pygmaeus) lost more than 100,000 individuals in the past 16 years [2] and declined by at least 25% over the past 10 years [3]. Furthermore, recent work has also demonstrated that both Sumatran orangutans (P. abelii) and the recently described Tapanuli orangutan (P. tapanuliensis) lost more than 60% of their key habitats between 1985 and 2007, and ongoing land use changes are expected to result in an 11-27% decline in their populations by 2020 [4,5].…”
mentioning
confidence: 92%